2022
DOI: 10.1038/s41598-022-17319-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between MR and CT imaging used to correct for skull-induced phase aberrations during transcranial focused ultrasound

Abstract: Transcranial focused ultrasound with the InSightec Exablate system uses thermal ablation for the treatment of movement and mood disorders and blood brain barrier disruption for tumor therapy. The system uses computed tomography (CT) images to calculate phase corrections that account for aberrations caused by the human skull. This work investigates whether magnetic resonance (MR) images can be used as an alternative to CT images to calculate phase corrections. Phase corrections were calculated using the gold st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…44 Most recently, Leung et al generated skulls from UTE images and calculated phases from the Insightec system but applied phases in a water bath setup, measuring the pressure field behind a skull using a hydrophone; they reported comparable beam profile results when compared with rCTs. 45 Regarding peak intracranial pressure differences observed between rCT and sCT, the mean difference computed in our study falls within an expected range of variability of 10% that was observed through an intercomparison study across 11 simulation tools. 46 Because the modeled array was large, the grid size necessary to fit all elements would be ðNx; Ny; NzÞ ¼ ð960; 960; 540Þ to maintain >6 PPW in water at 650 kHz and satisfy 3D convergence testing requirements to avoid simulation instabilities.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…44 Most recently, Leung et al generated skulls from UTE images and calculated phases from the Insightec system but applied phases in a water bath setup, measuring the pressure field behind a skull using a hydrophone; they reported comparable beam profile results when compared with rCTs. 45 Regarding peak intracranial pressure differences observed between rCT and sCT, the mean difference computed in our study falls within an expected range of variability of 10% that was observed through an intercomparison study across 11 simulation tools. 46 Because the modeled array was large, the grid size necessary to fit all elements would be ðNx; Ny; NzÞ ¼ ð960; 960; 540Þ to maintain >6 PPW in water at 650 kHz and satisfy 3D convergence testing requirements to avoid simulation instabilities.…”
Section: Discussionsupporting
confidence: 80%
“…5 Similar work has evaluated the skull correction performance capabilities of artificial skulls and applied the phases in an experimental context beyond modeling and simulations. 4,44,45 One study reconstructed a virtual CT from a T1-weighted MR image and compared calculated phases from Insightec's ExAblate system, resulting in an average phase difference between the real and MR-generated CT of <1 radians, and application of the phases was successfully demonstrated in thermal experiments using head phantoms. 4 A study using the same transducer as Wintermark et al compared UTE-derived MR images with rCT images of head phantoms and found no statistical difference between peak temperatures achieved for thermal experiments.…”
Section: Discussionmentioning
confidence: 99%
“…72(±18)%, followed by the transcranial modeling with 24(±16)% and thermal modeling with 4(±5)%. While some tasks in the domain generation are GPU-accelerated, such as voxelization and median filters, functions for bias correction, coregistration, and upscaling [36], Fry [38], Gimeno [34], Leung [33], Marsac…”
Section: Resultsmentioning
confidence: 99%
“…A pressure transmission coefficient T S was calculated with T S = √ E L . The values of T S calculated with each of the different mapping approaches were compared against experimental values of sub-MHz pressure transmission (T E ) from literature reports on pressure [18,29,[32][33][34][35][36] and energy [28,37,38] transmission. For the latter, T E was approximated by the square root of the reported energy transmission.…”
Section: Modelingmentioning
confidence: 99%
See 1 more Smart Citation